A Potential Link Between Prolonged Cork Exposure and Intestinal-Type Sinonasal Adenocarcinoma – Special Findings of a Retrospective Cohort Analysis - Alpuim Costa, D (2020)
Introduction: intestinal-type sinonasal adenocarcinoma (ITAC) is a rare epithelium tumor of the nasal cavities and paranasal sinuses. Exposure to wood and leather dusts is a strong etiological factor related to its development. Prolonged cork exposure has rarely been associated. Materials and methods: thirty-seven-year (1981-2018) retrospective cohort analysis of all consecutive patients with sinonasal cancer (SNC) followed at our institution. Medical records were reviewed to determine patient demographics, occupational/environmental exposure, location and extent of the tumor, stage, histopathology findings, treatment strategies, and oncologic outcomes. Survival analysis was done using Kaplan-Meier method. Results: we evaluated 379 patients with SNC, including 39 (10.3%) ITAC. Patient median age was 73 years (range 49-87), 56% male and 69% with identified professional occupational exposure (54% for cork; 69.2% considering only those for which an agent has been identified). Seventy-two percent had locally advanced disease (stage III or IVA-B). The initial treatment was surgery in 77%, and 54% received adjuvant radiotherapy. The median time to progression, progression-free survival, and overall-survival was 2.36 years (95% CI 1.54-8.70), 1.96 years (95% CI 1.43-3.74), and 3.51 years (95% CI 2.33-10.02), respectively. Conclusion: ITAC is an uncommon malignancy that grows silently, which contributes to delayed diagnosis, advanced stage and low survival rates. In our cohort, we observed a high prevalence of cork occupational exposure. This finding may lead to the implementation of protection measures and suggest a potential link to be further studied.